Chronic CD40L blockade is required for long-term cardiac allograft survival with a clinically relevant CTLA4-Ig dosing regimen - Unger, Lukas W.; Muckenhuber, Moritz; Mahr, Benedikt; Schwarz, Christoph; Pilat, Nina; Granofszky, Nicolas; Regele, Heinz; Wekerle, Thomas (Frontiers in Immunology, 2022)
Introduction In de-novo kidney transplantation, the CTLA4-Ig fusion protein belatacept is associated with improved graft function but also an increased risk of acute rejection compared to calcineurin inhibitor therapy. The combination with a second costimulation blocker could potentially improve outcome while avoiding calcineurin inhibitor toxicity. The aim of this study was to define the conditions under which the combination of CTLA4-Ig and CD40L blockade leads to rejection-free permanent graft survival in a stringent murine heart transplantation model. Methods Naïve wild-type or CD40L (CD154) knock-out mice received a fully mismatched BALB/c cardiac allograft. Selected induction and maintenance protocols for CTLA4-Ig and blocking αCD40L monoclonal antibodies (mAB) were investigated. Graft survival, rejection severity and donor-specific antibody (DSA) formation were assessed during a 100-day follow-up period. Results and Discussion Administering αCD40L mAb as monotherapy at the time of transplantation significantly prolonged heart allograft survival but did not further improve the outcome when given in addition to chronic CTLA4-Ig therapy (which prolongs graft survival to a median of 22 days). Likewise, chronic αCD40L mAb therapy (0.5mg) combined with perioperative CTLA4-Ig led to rejection in a proportion of mice and extensive histological damage, despite abrogating DSA formation. Only the permanent interruption of CD40-CD40L signaling by using CD40L-/- recipient mice or by chronic αCD40L administration synergized with chronic CTLA4-Ig to achieve long-term allograft survival with preserved histological graft integrity in all recipients without DSA formation. The combination of α-CD40L and CTLA4-Ig works most effectively when both therapeutics are administered chronically.